Medication Adherence and its Determinants among Type 2 Diabetic Patient in Tertiary Care Hospital - Shah, Pammi; K.C, Nyamika; Dhami, Kabita; Shah, Nisha Kumari; K.c, Mamta; Pokhrel, Khushi (Journal of Nobel Medical College, 2024)
Background: Diabetes mellitus imposes vast social, health, and economic impacts on individuals and countries in the long term.Inadequate medication adherence is a major factor leading to poor and suboptimal glycemic control among patients with DM, which catalyzes the magnitude of this problem and leads to the development of diabetic-related complications. Materials and Methods: A descriptive cross-sectional study was conducted in medicine and endocrine OPD of Nobel Medical College Teaching Hospital.A convenience sampling technique was deployed using a structured interview schedule consisting of a medication adherence scale having a 4 Likert scale. Data was analyzed by SPSS version 20.0. Descriptive statistics including, frequencies, percentages, mean, and standard deviation were demonstrated by using tables and pie charts. Inferential statistics were used to find out the association between the level of adherence and selected variablesand also determinants associated with non-adherence. Results: From a total of 228 study respondents, more than half (59.65%) of them were non-adherent to their anti-diabetic medication. Glycemic control and the type of drug taken were found to be significantly associated with the level of medication adherence. Patients with tend to forgetfulness, far distance from health facilities, fear of dependency on drugs, and symptoms of hypoglycemia will likely have greater odds to be non-adhered to medications. Conclusion: Medication adherence among diabetic patients in the present study is non-adherent. Glycemic control and the type of drug taken were associated with level of adherence